Women’s exposure to intimate partner violence and its association with child stunting: findings from a population-based study in rural Rwanda - Jean Nepo Utumatwishima; Ingrid Mogren; Kristina Elfving; Aline Umubyeyi; Ali Mansourian; Gunilla Krantz (Global Health Action)
Background Child stunting is a significant challenge for most districts in Rwanda and much of sub-Saharan Africa and persists despite multisectoral efforts. There is a notable lack of population-based studies examining the correlation between violence against women and child stunting in Rwanda. Objective We aimed to investigate the association between Rwandan women’s exposure to intimate partner violence (IPV) and child stunting in children under 3 years of age. Methods In December 2021, a population-based cross-sectional study was conducted in the Northern Province of Rwanda, including 601 women and their children <3 years of age. The World Health Organization (WHO) Women’s Health and Life Experiences Questionnaire for IPV research was utilized. Child stunting was assessed using the WHO criteria for low height for age. Multivariable logistic regression was used to examine the association between IPV and child stunting before and during pregnancy. Results Of 601 women, 47.4% (n = 285) experienced any form of IPV during pregnancy. The prevalence rates of the types of IPV associated with child stunting varied: 33% for psychological, 31.4% for sexual, and 25.7% for physical violence. Exposure to physical violence before pregnancy and sexual violence during pregnancy was associated with higher odds of child stunting; the adjusted odds ratios were 1.29 (95% CI, 1.01–2.03) and 1.25 (95% CI, 1.04–2.01), respectively. Conclusion Women’s exposure to physical and psychological violence is associated with an increased risk of child stunting. Urgent targeted interventions and support systems are needed to address the complex relationship between women’s exposure to IPV and adverse effects on child growth.